Oviposition choice and larval performance of Neomusotima conspurcatalis on leaflet types of the invasive fern, Lygodium microphyllum. Issue 1 (7th July 2016) - Smith, Melissa C.; Lake, Ellen C.; Wheeler, Gregory S.
Abstract: Lygodium microphyllum (Cavanilles) R Brown (Lygodiaceae), Old World climbing fern, invades wildlands in central and southern Florida, USA, and causes considerable habitat disturbance. Efforts to develop an effective biological control strategy have focused on several folivorous insects and a leaf‐galling mite from southeast Asia and Australia. Neomusotima conspurcatalis Warren (Lepidoptera: Crambidae) is a foliage‐feeding moth that specializes on Lygodium species. First released in 2008, N. conspurcatalis successfully established in Florida and is dispersing throughout the L. microphyllum‐ invaded range. We investigated whether N. conspurcatalis display any preference (oviposition or larval feeding) between two leaflet morphologies, i.e., fertile spore‐producing vs. sterile leaflets. Furthermore, we examined whether oviposition and no‐choice diets on either fern leaflet type conferred any possible selective advantages (e.g., weight, emergence success) to the offspring. Finally, we analyzed leaf nitrogen and carbon content and leaf volatiles to gauge differences between the leaflet types. In choice and no‐choice scenarios, larvae consume approximately the same amount of leaf area and display no preference between fertile and sterile leaflets. However, females deposited significantly more eggs on fertile than on sterile leaflets. Oviposition choice had no effect on larval development times, pupal weights, or successful eclosure. Nitrogen and carbon content did not differ between fertile and sterile samples, but sterile leaflets contain more 1‐octen‐3‐ol, which may act as an herbivory deterrent. The propagule attack imposed by N. conspurcatalis feeding on fertile leaflets is unlikely to provide adequate control, but could be beneficial as part of a suite of biological control agents and other control methods.